Penerapan Pembelajaran Daring Berbasis Whatsapp Group Untuk Siswa Madrasah Ibtidaiyyah di Tengah Pandemi Covid-19 - Laelasari, Iseu; Dewi, Nofita Puspa (LP2M IAIN kUDUS, 2020)
This study aims to describe the application of whatsapp group online learning for Madrasah Ibtidaiyyah students in the middle of the covid-19 pandemic at MI NU Nurus Shofa Kudus. Researchers use qualitative descriptive methods. In this study the methods of data collection were observation and interviews. Research indicates that almost most of MI NU Nurus Shofa's teachers carried out online studies in the middle of the covid-19 pandemic. As for the most widely used application in promoting online learning the whatsapp application, for then the whatsapp group is created. A teacher's material delivery is by having his students look at TVRI television and read the LKS book according to his subject. The methods of learning used are assignments and practices, the learning media used is a mobile phone using a whatsapp application, while the learning model is used a video. The problem students are experiencing is that they have not been able to use the whatsapp application, to send assignments, to do the problem, to understand the material, and to limit access to the Internet. In this case it takes a teacher's creativity to achieve the purpose of learning.